Ex ante impact assessment of disease control technologies: The case of vector-borne infections in Africa - Perry, Brian D.; Kruska, Russell L.; Medley, G.F.; Mukhebi, A.W.; O'Callaghan, C.J.; Peter, T.F.; Reid, Robin S.; Williams, T. (1997)
The International Livestock Research Institute (ILRI) conducts research on strategic issues that constrain livestock productivity of resource-poor households, with a focus as smallholder crop-livestock systems. The institute conducts research in the areas of ruminant genetics, ruminant health, feed resources, crop-livestock systems and strengthening national agricultural systems of the developing world. Although previously concerned principally with Africa, the Institute now has a global mandate and is initiating research in Asia and Latin America. With such a broad mandate and geographical coverage, it is imperative that the institute develops a strategic focus, undertaking research on issues that are demonstrated to be of high priority, and ensuring research products reach its clients and beneficiaries. As a result, there has been an increasing demand for ex ante impact assessment in two areas. The first is to predict the potential returns to research in different subjects, so contributing to priority setting for livestock research. The second, the subject of this paper, is to predict the impact of the products of current research, in order that continued investment in such research can be justified, and that such research products achieve their optimal impact on livestock productivity. In the area of animal health research, ILRI focuses on haemoparasitic infections of ruminants, in particular the tick-borne infections and the trypanosomoses. Ex ante impact assessment of new technologies to control these diseases has become an important area of research itself (Perry, 1996). Three examples of impact assessment are presented in this paper, describing studies to evaluate the impact of diseases and their control on biological, economic and environmental indicators. These three cases are: Predicting the infection dynamics of heartwater, predicting the economic impact of new theileriosis vaccines, and predicting the environmental impacts of trypanosomosis control.